Assessment of Hydrocarbonoclastic Microorganisms from Selected Mechanic Workshops in Nigeria - Adaeze Chiemela; Ugochukwu Okafor; Abba Oluchukwu (Malaysian Journal of Science and Advanced Technology)
Microorganisms are particularly adept at breaking down complex organic compounds into simpler, less harmful substances through processes like biodegradation and thereby offer a promising solution to the challenges posed by industrial pollutants. This study focused on the assessment of hydrocarbon-utilizing microorganisms in selected mechanic workshops within Awka Town, Anambra State and it aimed to identify microbial species capable of degrading hydrocarbons, particularly in environments impacted by automotive activities. The research methodology involved sample collection, microbial isolation, and characterization, utilizing both traditional and culture-based techniques. To achieve this, samples were collected from the workshop sites, and the isolated microorganisms were scrutinized for their hydrocarbon-degrading potential. Screening for hydrocarbonoclastic microorganisms in oil-polluted soil from mechanic workshops resulted in the isolation of bacterial, yeast, and mold strains. The identification of fast-growing Pseudomonas aeruginosa and Bacillus subtilis, along with a suspected strain of Rhodococcus spp., in the oil-polluted soil reinforced the report of the potential for these microorganisms in bioremediation efforts. The dominant mold was Aspergillus spp., known for their resilient spores suited for harsh condition, while Candida spp., was the dominant yeast genera.